Consumption of low-calorie sweetened drinks is associated with 'sweet satiation', but not with 'sweet-taste confusion': A virtual study. (1st November 2022) - Monge, Angelica M.; Ferriday, Danielle; Heckenmueller, Simon; Brunstrom, Jeffrey M.; Rogers, Peter J.
Abstract: Originating from studies on rats, the 'taste confusion' hypothesis predicts that exposure to low-calorie sweeteners (LCS) will impair compensatory responses to sugar intake, resulting in increased overall calorie intake. We conducted a virtual study in which young adult human participants (n = 332), who differed in their history of exposure to sweet drinks (e.g., drank 'diet' (LCS) soft drinks or 'regular' (sugar-sweetened) soft drinks), imagined consuming a cheese sandwich and two-thirds of a 500 ml drink (still water, sparkling water, diet Coca Cola, regular Coca Cola, or semi-skimmed milk), or no drink, as a hypothetical lunch-time meal. They then used a screen-based tool to select the amount of a sweet snack (chocolate M&M's) or savoury snack (salted peanuts) that they would eat immediately with the remaining third of their drink (i.e., a total of 12 drink and snack combinations per participant). The results were inconsistent with the predictions of the taste confusion hypothesis; specifically, the extent to which consumption of sugar cola compared with water (still or sparkling) reduced snack intake did not differ between habitual diet (LCS) and habitual sugar soft-drink consumers. Other results showed a 'sweet satiation' effect (i.e., lower sweet versus savoury snack intake when the drink accompanying the meal was sweet compared with when it was water), and negligible compensation in snack food intake for the difference in the energy content of diet versus sugar cola.